Remission of anorexia nervosa after thyroidectomy: A report of two cases with Graves' disease and anorexia nervosa - Noguchi Hitoshi; Murakami Tsukasa; Uchino Shinya; Yamashita Hiroto; Noguchi Shiro (Thyroid Research, 2011)
Abstract We report two patients with anorexia nervosa and Graves' disease who received subtotal thyroidectomy for Graves' disease and concomitantly experienced remission from anorexia nervosa. Both were young women (aged 20 and 26) at the time of surgery. Both had well controlled thyroid function and eating behavior at the time of surgery. Both were followed for over five years without relapse of anorexia nervosa or hyperthyroidism. These cases suggest the existence of an endocrine factor originating from the thyroid gland that is involved in the pathogenesis of anorexia nervosa. Since patients of thyroidectomy can remain in good health with supplement of thyroxine alone, it can be hypothesized that this anorexigenic endocrine factor is an evolutionary relic not necessary for the normal function of humans and does not have physiological effects unless secreted beyond normal levels. Given that, it implies the existence of a creature in the animal kingdom for which such an anorexigenic hormone is essential for survival. Migrating birds eat beyond their caloric expenditure before migration and become anorexic for the duration of their flight. It is also known that their thyroid function is elevated during migration. The normal physiology of migration is a complex mechanism involving the hypothalamic, pituitary, thyroid, adrenal and reproductive hormones. The mechanism of disease, however, can be simpler. A review of the literature is presented that suggest a heretofore unreported thyroid hormone, which is involved in the regulation of migration behavior, may be the responsible factor behind anorexia nervosa.